2015
DOI: 10.1080/13825585.2015.1041450
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve and cognitive function in healthy older people: a meta-analysis

Abstract: The associations between proxy measures of cognitive reserve (CR) and cognition vary across studies and cognitive domains. This meta-analysis aimed to assess the relationship between CR and cognition in multiple domains (memory, executive function, visuospatial ability, and language). CR was considered in terms of three key proxy measures-educational level, occupational status, and engagement in cognitively-stimulating activities-individually and in combination. One-hundred and thirty-five studies representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

47
263
3
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(329 citation statements)
references
References 89 publications
47
263
3
16
Order By: Relevance
“…Furthermore, in line with prior evidence [6,14,15], we found that higher educational attainment, greater engagement in a broad variety of leisure activities, and higher cognitive level and lower physical demand of individuals' occupation were related to a better performance in all three investigated cognitive performance measures in old age. This confirms the conceptual view that cognitive stimulation throughout the life course may contribute to cognitive reserve, thereby being related to better cognitive functioning in old age [3,4,14,15]. …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, in line with prior evidence [6,14,15], we found that higher educational attainment, greater engagement in a broad variety of leisure activities, and higher cognitive level and lower physical demand of individuals' occupation were related to a better performance in all three investigated cognitive performance measures in old age. This confirms the conceptual view that cognitive stimulation throughout the life course may contribute to cognitive reserve, thereby being related to better cognitive functioning in old age [3,4,14,15]. …”
Section: Discussionsupporting
confidence: 78%
“…This view is supported by findings that engaging in a variety of leisure activities and pursuing an occupation with a high cognitive level lead to enrichment effects, make a contribution to cognitive reserve throughout a person's lifetime, and are related to better cognitive functioning (i.e. better processing speed, memory, and executive functioning) in old age [4,10,11,12,13] (see [14] for a review on enrichment effects in adulthood; see [15] for a recent meta-analysis).…”
Section: Introductionmentioning
confidence: 99%
“…In individuals with healthy cognitive functioning, these mechanisms contribute to the adaptation of brain activity when the task difficulty level is increased and thereby enhance cognitive performance [4]. Empirically corroborating the predictions of the cognitive reserve concept, evidence showed that longer education in early life, cognitively demanding jobs in midlife, and leisure activities in midlife and old age contribute to cognitive reserve during the life course and are related to better cognitive functioning such as memory and executive functioning in old age [5-17]. Another research line related to the concept of reserves concerns social capital [18, 19].…”
Section: Introductionmentioning
confidence: 85%
“…Previous studies have used an IQ estimate as proxy for CR (Alexander et al, 1997;Farinpour et al, 2003;Galioto, Alosco, Spitznagel, Stanek, & Gunstad, 2013), however often a combination with education level, occupational attainment, and engagement in cognitively stimulating leisure activities is used (Opdebeeck, Martyr, & Clare, 2016). As such, also in our study a higher IQ estimate may be indicative of higher levels of CR.…”
Section: Discussionmentioning
confidence: 55%